2018
DOI: 10.1186/s40886-018-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment and management of trauma patients in an emergency department of a tertiary hospital in Tanzania

Abstract: Background: Proper pain assessment is a core component in management of trauma patients but prior literature has suggested that pain management is inadequate in emergency settings. With the development of emergency medicine in low-income countries (LIC), the procedures for pain assessment and management of trauma patients have not been well studied and protocols have not been established. We aimed to describe practices of pain assessment and management in an emergency department in Tanzania. Methods: This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The primary basis for pain relief is the administration of systematic analgesic agents or non-steroidal anti-in ammatory drugs (NSAIDs) [24][25][26]. In one study from a low-income country, it was found that less than half of patients with documented pain received medication for pain at ED; also, it was stated that high-income countries suffer improper management of pain in traumatic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The primary basis for pain relief is the administration of systematic analgesic agents or non-steroidal anti-in ammatory drugs (NSAIDs) [24][25][26]. In one study from a low-income country, it was found that less than half of patients with documented pain received medication for pain at ED; also, it was stated that high-income countries suffer improper management of pain in traumatic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, admission to hospital may lead to depression as it disrupts usual life and there is the prospect of medical or surgical interventions as well as loss of independence and body image [ 4 , 5 ]. In addition, anticipated surgery and anesthesia is the major stress factors for patients scheduled for surgery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%